2013
DOI: 10.1099/ijs.0.043729-0
|View full text |Cite
|
Sign up to set email alerts
|

Tepidimonas fonticaldi sp. nov., a slightly thermophilic betaproteobacterium isolated from a hot spring

Abstract: A slightly thermophilic bacterial strain, designated AT-A2 T , was isolated from a hot spring water sample taken from the Antun hot spring in Taiwan and characterized using a polyphasic taxonomic approach. Cells of strain AT-A2 T were aerobic, Gram-negative, motile by a single polar flagellum and formed non-pigmented colonies. Growth occurred at 35-60 6C (optimum, 55 6C), with 0-1.0 % NaCl (optimum, 0.2 %) and at pH 7.0-9.0 (optimum, pH 7.0). Phylogenetic analyses based on 16S rRNA gene sequences showed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This bacterium grows aerobically on organic acids (acetate, lactate, and pyruvate) and amino acids within a broad temperature range from 35 to 60°C (with the optimum at 55°C), at low ambient salinity and neutral pH, and is capable of nitrate reduction (Chen et al, 2013). No data are presently available concerning its ability to utilize components of crude oil.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium grows aerobically on organic acids (acetate, lactate, and pyruvate) and amino acids within a broad temperature range from 35 to 60°C (with the optimum at 55°C), at low ambient salinity and neutral pH, and is capable of nitrate reduction (Chen et al, 2013). No data are presently available concerning its ability to utilize components of crude oil.…”
Section: Discussionmentioning
confidence: 99%
“…Tepidimonas taiwanensis and Tepidimonas fonticaldi are both thermophilic bacteria isolated from a hot spring of southern Thailand (Chen et al 2006) and Antun hot spring from Taiwan (Chen et al 2013). This study also identified few Tepidimonas OTUs in Jakrem 16S rRNA library.…”
Section: Discussionmentioning
confidence: 99%
“…T. ignava SPS-1037 T and T. sediminis YIM 72259 T have genes coding for the nitrate/nitrite transporters nasA/narK but the nitrate reductase complex narGHIJ was not identified in the genome sequences. Nitrate did not appear to be reduced by T. thermarum AA-1 T experimentally in one study but his strain has been reported to reduce nitrate in another study [4,5]. However, the genome predicts that nitrate should be reduced to nitrite because this organism possesses narGHIJ.…”
mentioning
confidence: 97%
“…html# tepidimonas). The genus comprises seven species with validly published names, Tepidimonas ignava [1], Tepidimonas aquatica [2], Tepidimonas taiwanensis [3], Tepidimonas thermarum [4] and Tepidimonas fonticaldi [5], Tepidimonas sediminis and Tepidimonas alkaliphilus [6], while the species 'Tepidimonas arfidensis' [7] has not been validly published.…”
mentioning
confidence: 99%
See 1 more Smart Citation